Implementation Of Character Education In Planting Student Nationalism In The Era Of Independent Learning - Edi Siswanto (Universitas Sebelas Maret, 2020)
Seeing the existing problems with the character crisis in this country, as an effort for social studies teachers to implement character education in instilling the nationalism of students in the era of independent learning. The method used in this research is a qualitative descriptive method, where descriptive research in this case is a study that aims to describe the policy of independent learning as an effort to improve the quality of education and the attitude of nationalism. The results of this study indicate that the attitude of nationalism which is part of the character values really needs to be possessed by students, the role of the teacher is very important in shaping the character of students who have a nationalistic attitude. The teacher's role implementation can be reflected in the teacher's personality, because the teacher is the main factor and influences the learning process of students. The efforts of history teachers in forming students' nationalistic attitudes, namely linking with the scope, historical material and lesson plans for history subjects, the methods used by teachers in instilling the existing values of nationalism. Learning media used by teachers in an effort to form student nationalism attitudes.